Efficacy and Safety of Denosumab in Osteoporosis or Low Bone Mineral Density Postmenopausal Women - Chen, Yi; Zhu, Jun; Zhou, Yiqin; Peng, Jinhui; Wang, Bo (Frontiers in Pharmacology, 2021)
Denosumab, a human monoclonal antibody, acts against the receptor activator of nuclear factor-κB ligand, and is a promising antiresorptive agent in patients with osteoporosis. This study aimed to update the efficacy and safety of denosumab versus placebo in osteoporosis or low bone mineral density (BMD) postmenopausal women. PubMed, EmBase, Cochrane library, and ClinicalTrials.gov were searched for randomized controlled trials (RCTs) reporting the efficacy and safety data of denosumab versus placebo in osteoporosis or low BMD postmenopausal women. A random-effects model was used to calculate pooled weight mean differences (WMDs) or relative risks (RRs) with corresponding 95% confidence intervals (CIs) for treatment effectiveness of denosumab versus placebo. Eleven RCTs including 12,013 postmenopausal women with osteoporosis or low BMD were preferred for final meta-analysis. The summary results indicated that the percentage change of BMD in denosumab group was greater than placebo at 1/3 radius (WMD:3.43; 95%CI:3.24-3.62; P<0.001), femoral neck (WMD:3.05; 95%CI:1.78-4.33; P<0.001), lumbar spine (WMD:6.25; 95%CI:4.59-7.92; P<0.001), total hip (WMD:4.36; 95%CI:4.07-4.66; P<0.001), trochanter (WMD:6.00; 95%CI:5.95-6.05; P<0.001), and total body (WMD:3.20; 95%CI:2.03-4.38; P<0.001). Moreover, denosumab therapy significantly reduced the risk of clinical fractures (RR:0.57; 95%CI:0.51-0.63; P<0.001), nonvertebral fracture (RR:0.83; 95%CI:0.70-0.97; P=0.018), vertebral fracture (RR:0.32; 95%CI:0.25-0.40; P<0.001), and hip fracture (RR:0.61; 95%CI:0.37-0.98; P=0.042). Finally, denosumab did not cause excess risks of adverse events. These findings suggested that postmenopausal women receiving denosumab had increased BMDs and reduced fractures at various sites without inducing any adverse events.